1988
DOI: 10.1017/s014134730001363x
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Behaviour Management in a Psychiatric Day Hospital

Abstract: If behaviour therapy is to remain viable and relevant, it needs to address key problems in the settings in which they arise. One major problem facing behaviour therapists is that of procuring institutional innovation. This study illustrates the successful application of an “organizational behaviour management” (OBM) approach within a psychiatric day hospital. The central issues of measuring and manipulating important system variables, and of relating these to clinical outcomes, are addressed by concurrent proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Through the feedback of group and individual WIB values the care team can see episodes of excellence as well as examples where care can be improved. The method can feed into care planning because it highlights in clear terms what needs to be carried out to improve the quality of daily life for the person with dementia and is a useful tool for organizational behaviour management (Milne 1988).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the feedback of group and individual WIB values the care team can see episodes of excellence as well as examples where care can be improved. The method can feed into care planning because it highlights in clear terms what needs to be carried out to improve the quality of daily life for the person with dementia and is a useful tool for organizational behaviour management (Milne 1988).…”
Section: Resultsmentioning
confidence: 99%
“…The method can feed into care planning as it highlights in clear terms what needs to be carried out to improve the quality of daily life for people with dementia. It is a useful tool for organizational behaviour management (Milne 1988) as well as meeting the demands of clinical governance. The DCM could therefore be an audit tool that is powerful at bringing about change within service systems.…”
Section: Resultsmentioning
confidence: 99%
“…The term "organizational behaviour management" (OBM) is used when assessment data are part of a systems-level intervention, and an attempt is made to analyse its functional relationship to an objective, such as a better service or better clinical outcomes (Krapfl, 1981). In an earlier study, Milne (1988) showed how OBM could be applied with some success in a psychiatric day hospital, using "ward atmosphere" data. He appealed to behaviour therapists to undertake more systems-level work of this kind, based on a logical extension of their clinical skills.…”
Section: Introductionmentioning
confidence: 99%